Approaches to Improving Nursing Handover in Surgical Wards Liaquat University Hospital Hyderabad - Photo; Chandio, Khushboo; Channar, Husan Bano; Samejo, Ubedullah; Mansoor ul Haque; Nasreen; Saleem, Imran (Indus Journal of Bioscience Research, 2025)
Background: Effective nursing handover plays a vital role in maintaining patient safety and ensuring continuity of care, especially in surgical wards, where patients often have complex medical needs. At Liaquat University Hospital (LUH) Hyderabad, handovers are often inconsistent and informal, which can lead to miscommunication, treatment delays, and negative patient outcomes. Objective: This study aimed to evaluate current nursing handover practices in the surgical wards at LUH Hyderabad, identify the main challenges faced by nurses, and explore practical strategies such as standardized formats and structured communication to improve the quality and safety of handovers. Methods: A descriptive cross-sectional study was carried out from February 10, 2025 to June 10, 2025, involving 90 nurses selected through purposive sampling. Data were gathered using a structured questionnaire divided into four sections: demographic details, current handover practices, challenges and quality of handovers, and suggestions for improvement. The data were analyzed using SPSS version 23 with descriptive statistics. Results: Of the 90 participants, most were staff nurses (53.3%) or nursing students (36.7%), and about one-third had 1–5 years of professional experience. The most common handover method combined verbal and written formats (44.4%), but only 40% used a structured tool like SBAR. Key obstacles included frequent interruptions (41.1%), time limitations (34.4%), and lack of proper training (34.4%). Just 41.1% of respondents felt that current practices effectively ensured patient safety. However, a large majority (81.1%) supported adopting SBAR, and popular suggestions for improvement included bedside handovers (33.3%) and the use of checklists (28.9%). Conclusion: The study revealed that nursing handovers at LUH Hyderabad are often unstructured, which compromises communication and patient safety. To address these gaps, there is a strong need for standardizing handovers through tools like SBAR, offering regular training, managing time more effectively, and improving the ward environment to support safer and more efficient communication.